The Social Use of Batonu Personal Names - Cecilia A. Ajiboye; Omobola A. Aladesanmi; Oluwatoyin M. O̩laiya (Universitas Sanata Dharma, 2020)
Previous researchers on the use of Batonu personal names argue that there are different categories of Batonu names and using thirty (30) respondents, the researchers submit that the use of Muslim names has replaced the use of Batonu native names in all domains. However, the present study, using three hundred (300) respondents, visited the study area and identifies names that are used as personal names among the Batonu people. It also examines the social use of the names in formal and informal domains. The research adopted the theory of Domains of language use by Ferguson (1966). Questionnaires and interviews were used to collect data on the various uses of personal names in intra and inter group interactions. There were three findings. Some showed names that were drawn from Islam and Christianity. Some names were also drawn from Batonu native names. Two domains of name usage have been identified. The informal domains consisted of home/community, peer-group and play ground. The formal ones comprised school, places of worship, certificates, wedding cards, almanacs and work places. It is evident that the Batonu native names are still frequently used with foreign or Christian and Muslim names in formal and in informal domains although with different degrees of use. This present study has shown that although a foreign culture may have an overwhelming influence over an indigenous culture, it does not mean that the indigenous culture will not thrive especially if the indigenous culture has traditional activities that can help sustain it.